IMPLEMENTATION OF RESPONSIVE ARCHITECTURAL CONCEPTS IN THE DESIGN OF THE CIKOLE FOREST RESORT, BANDUNG, WEST JAVA - Whinda Rofika Arofah; Asep Yudi Permana; Riskha Mardiana (Universitas Kebangsaan Republik Indonesia [UKRI], 2019)
Indonesia has a lot of potential for nature tourism in the form of mountains, sea, and beaches. This is also an attraction for tourists to make Indonesia as the preferred natural tourist destination when on vacation. Especially West Java, West Java is one of the provinces that are in great demand by local and outside tourists.Besides being famous for its local culture and its unique culinary variety, West Java is also known for its cool air, especially in some parts that are still preserved in nature, the natural potential that is still good and is maintained as an attraction for West Java to attract tourists. One of the famous areas in the city of Bandung which is a tourist destination is the Lembang Region.From the last five years the lodging area in Lembang has increased, currently in Lembang sub-district itself has 13 lodging units in the form of resorts. The amount itself is influenced by the high demand for lodging accommodation especially when the holiday season arrives. But of that number, resorts that have complete and well-maintained facilities and conditions are still not completely even. Based on this fact, the purpose of designing this resort is expected to be the best tourist area in the region to be able to adjust to the conditions of the land conditions, be able to use and not damage the existing land on the design land.The study used in this design is based on the description that occurs today with the support of the literature that supports the theory and analysis that is done. Implementation analysis was carried out using macro and microanalysis methods. Macro analysis is an analysis on a regional scale. While microanalysis is an analysis of the design site, which includes activity analysis, function analysis, space analysis, site analysis, shape analysis, and display and structural analysis and utility.The concept of site and building in this design will produce a conceptual relationship that will later become a guideline in making a design. This concept includes the proposed concept of site design, form, structure, and utility.